Social ties, clientelism, and the poor's expectations of future service provision: Receiving more, expecting less? - Prisca Jöst; Ellen Lust-Okar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Are candidates who hand out clientelistic goods at election time less likely to provide services once they take office? This paper examines the poor's expectations of future service provision by candidates who hand out money and other goods versus those who do not. We hypothesize that the poor's expectations should depend on the density of social ties. To test this hypothesis, we use hierarchical models to analyse observational data and two conjoint experiments embedded in a unique survey of Kenyans, Malawians, and Zambians. The heavily clustered sampling design allows the investigation of community- and individual-level factors, while the large sample size allows us to focus on a subsample of over 14,000 poor respondents. In socially dense communities, we find that monetary handouts signal the candidate's ability to provide future services; in less socially dense areas, such handouts appear to be viewed as in lieu of future services. Greater information flows in socially dense communities may help poor voters to monitor candidates and hold them accountable. It is important to consider how communities' experiences with clientelism affect expectations of service provision. Development practitioners need to understand how social context affects not only the likelihood of vote-buying but also the distributive effects of clientelism.
Keywords: 330; vote-buying; clientelism; social ties; poverty; service provision